Factors predicting recycling behaviour among Malaysian - Jasmine Adela Mutang; Sharifah Azizah Haron (Southeast Asia Psychology Journal, 2012)
Malaysia is facing a crisis in solid waste management due to rapid urbanization and high concentration of population. Sadly, public participation in recycling is still very low despite rigorous campaigns conducted by the government. Only a small amount of solid waste generated in Malaysia is recycled – far below the rate of 15 to 40 percent in developed countries. This study examines the recycling behaviour among urban households within the Klang Valley area. Specifically, the purpose of the study is to determine factors that increase the probability of recycling behaviour among households. Data analysis technique used consisted of bivariate analysis and logistic regression. The results of logistics regression testing for socio-demographic and psychological characteristics show partial significance at a probability level of .050. The result of Hosmer and Lamershow Goodness-of-fit shows total significance at .050. The logistic model that utilizes study data drawn from the 342 samples and the results of the Binomial Logistic Regression indicate that recycling increased among respondents who are married, possess higher education levels have positive values towards the environment and positive attitudes towards recycling. Interestingly, gender, different types of employment status, types of accommodation, house ownership, and knowledge of recycling were not reliable predictors of recycling behaviour. The findings of the study could be used for designing recycling schemes although it is clear that a one-size-fits-all approach is not acceptable.